Pengelolaan Kelas dengan Menerapkan Aplikasi AR di Sekolah Dasar - Jumriani Jumriani; Tarman A. Arif; Tasrif Akib (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Effective classroom management is very important to create a conducive learning environment for students, especially in elementary schools. Along with technological developments, Augmented Reality (AR) applications have emerged as a tool that can increase interactivity and attractiveness in the learning process. This article discusses the application of AR applications in classroom management in elementary schools to increase students' interest, motivation and understanding of subject matter. AR applications allow students to interact directly with virtual objects that enrich their learning experience, both in visual and kinesthetic learning. The main benefits of using AR include increased student engagement, visualization of complex material, and more structured and engaging classroom management. However, its implementation also faces challenges such as limited technological infrastructure and training needs for teachers. This research suggests that schools can prepare supporting devices and provide adequate training to teachers to optimize the use of this technology in learning. Thus, AR applications can be an innovative solution in creating a more interesting and effective learning experience in elementary schools.